The Implementation of Teaching Speaking Using Task-Based Approach in Indonesian Secondary School EFL Classes: The State of The Art - Hibatulloh, Muhammad Firnas; Arganata, Koko Lintang; Latifah, Chyntia Nur; Kurniasari, Ulfa (Institut Agama Islam Negeri (IAIN) Kediri, 2024)
The demand for English proficiency in global communication has led to a heightened focus on language skills, particularly speaking. This study explores the implementation of Task-Based approach in Indonesian secondary school English as a Foreign Language (EFL) classes, specifically emphasizing speaking skills. Drawing from a systematic literature review, the study addresses three key aspects: the practice of teaching speaking using the task-based approach, perceptions of students and teachers towards task-based approach, and the development and evaluation of task-based speaking materials. The findings indicate widespread adoption of task-based approach in various school contexts, showcasing its effectiveness in enhancing students' speaking skills. However, challenges such as time constraints, pronunciation difficulties, and occasional boredom have been noted. Students generally hold positive perceptions, noting improvements in pronunciation, vocabulary, and overall interest in English learning. Teachers, while acknowledging the positive impact, face challenges in finding suitable tasks for diverse student backgrounds and express a need for adequate training. The study also highlights the development of task-based speaking materials, catering to diverse learning styles and instructional goals. Continuous adaptation, teacher training, and the development of contextually relevant materials are essential for its sustained success. The study provides valuable insights for English teachers, curriculum developers, and policymakers seeking to optimize language education in the Indonesian context.